FINANCIAL DETERMINANTS OF CARRY TRADE ACTIVITY - Czech, Katarzyna; Waszkowski, Adam (Acta Scientiarum Polonorum. Oeconomia, 2012)
Recently, the yen carry trade is perceived to be one of the most widely used currency speculation strategy. The aim of the paper is to examine the relationship between the yen carry trade activity and the related variables. The study is focused on the Japanese and U.S. financial variables. It is assumed that carry trade activity is affected by the interest rate differential between U.S. and Japan, JPY/USD exchange rate and the S&P 500 option implied volatility index (VIX). The paper investigates above relationship by the structural vector autoregression (SVAR) model. The results suggest that JPY/USD exchange rate is the only variable which has a significant impact on carry trade activity. It is shown that the depreciation of Japanese yen against U.S. dollar leads to the increase in yen carry trade activity.